EFFECTS OF PHYSICAL ACTIVITY ON THE ACADEMIC PERFORMANCE AMONG THE UNDERGRADUATE STUDENTS OF COLLEGE OF NURSING SIR C, J INSTITUTE OF PSYCHIATRY AND BEHAVIORAL SCIENCES HYDERABAD (Journal of Medical & Health Sciences Review, 2025)
Background: Physical activity is widely recognized for its beneficial effects on mental health and academic performance. This study aimed to explore the effects of physical activity on the academic performance of undergraduate nursing students at the College of Nursing, Sir C. J Institute of Psychiatry and Behavioral Sciences, Hyderabad. Methods: A descriptive cross-sectional study was conducted between May and July 2025 among Bachelor of Science in Nursing students from all academic years. Using a convenience sampling technique, data were collected through a structured, self-administered questionnaire, which included sections on demographic characteristics, physical activity levels, and self-perceived academic performance. Ethical approval was secured, and informed consent was obtained from all participants. Data were analyzed using SPSS version 26, employing descriptive statistics such as frequencies and percentages. Results: The mean age of participants was 27.8 years (SD = 2.537), with a male predominance (90.2%). Approximately 26.6% of students reported engaging in daily physical activity, while 22.9% were inactive. Academic workload was the most frequently reported barrier to physical activity. More than half of the students did not track their activity, yet many perceived a positive impact on both mental well-being and academic performance. Notably, 26.2% reported slight improvement, and 24.8% reported significant improvement in academic performance due to physical activity. Conclusion: The findings indicate a positive association between physical activity and perceived academic performance. Institutions should consider incorporating physical activity promotion into the curriculum to enhance student well-being and academic outcomes.